Perceived Stress and Internet Addiction Among Chinese College Students: Mediating Effect of Procrastination and Moderating Effect of Flow - Gong, Zhun; Wang, Liyun; Wang, Haijiao (Frontiers in Psychology, 2021)
Perceived stress, Internet addiction and procrastination are common issues among college students. Based on compensatory network using model and emotion regulation theory, this study aims to explore two possible mechanisms for the connection between perceived stress and Internet addiction: mediating effect of procrastination and moderating effect of flow experience on the Internet. Cross-sectional design and questionnaire survey were used in this study. Data were collected from 446 college students who voluntarily completed self-reporting of perceived stress, internet addiction, procrastination and flow. A potential mediation and moderation model between variables was calculated during the process. The results revealed that there were significant associations among perceived stress, Internet addiction, procrastination and flow. The results also showed that procrastination plays a mediating role between perceptual stress and Internet addiction. While, flow plays a moderating role between them. The results emphasized the importance of the intention behind college students' overuse of the Internet. These results also provided a perspective of finding the possible causes of Internet addiction in college students, that is, individuals use the Internet to procrastinate in order to avoid perceived stress, and the flow experience on the Internet also has an impact on this process.